1975
DOI: 10.1159/000231461
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Formation and Release of Bovine SRS-A <i>in vitro</i> by several Anti-Anaphylactic Drugs

Abstract: Abstract. Slow-reacting substance of anaphylaxis (SRS-A) is released immunologically from bovine lung in vitro. Various drugs known to protect calves and other animals during anaphylaxis were tested to investigate their modulation of the for mation and release of SRS-A. The anti-inflammatory drugs, meclofenamate and as pirin, potentiated SRS-A release. Chlorphenesin and diethylcarbamazine citrate at high concentrations both inhibited SRS-A release. Two new anti-anaphylactic drugs, PR-D-92-EA and M&B 22,948, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1976
1976
1988
1988

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 6 publications
(8 reference statements)
1
21
0
Order By: Relevance
“…Because indomethacin enhanced the postcapillary leakage to ovalbumin also in mepyramine-treated animals, modulated release of other mediators such as leukotrienes C4, D4, and E4 may have contributed, as indicated by studies in vitro (18,20,22,23). However, neither histamine nor cysteinyl-leukotrienes mediate the leukocyte accumulation and associated leakage of plasma enhanced by indomethacin, a phenomenon predicted to require increased release of chemotactic mediator(s).…”
Section: Resultsmentioning
confidence: 99%
“…Because indomethacin enhanced the postcapillary leakage to ovalbumin also in mepyramine-treated animals, modulated release of other mediators such as leukotrienes C4, D4, and E4 may have contributed, as indicated by studies in vitro (18,20,22,23). However, neither histamine nor cysteinyl-leukotrienes mediate the leukocyte accumulation and associated leakage of plasma enhanced by indomethacin, a phenomenon predicted to require increased release of chemotactic mediator(s).…”
Section: Resultsmentioning
confidence: 99%
“…It has earlier been reported that DECC inhibits responses to histamine and 5-HT (Burka & Eyre, 1974) and the Schultz-Dale reaction (Eyre, 1971). High doses of DECC have been reported to inhibit immunological release of SRS-A (Orange et al, 1968;Burka & Eyre, 1975) and the inhibition of the Schultz-Dale phenomenon by large doses of DECC appears to suggest the formation and release of SRS-A from intestinal tissues but lack of specificity of DECC on a variety of exogenous agonists makes such a conclusion tenuous. Furthermore, antigen-induced release of SRS-A and histamine from chicken lung and intestine in vitro could not be demonstrated (Chand & Eyre, unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of the Schultz-Dale reaction by this compound may be due to the inhibition of formation and release of histamine and SRS-A (Broughton et al, 1974;Burka & Eyre, 1975) by virtue of blocking cyclic 3',5'-adenosine monophosphate phosphodiesterase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitors of the cyclo-oxygenase pathway of arachidonic acid metabolism enhance immunological SRS-A release from the lungs of man (Walker, 1972), ox (Burka & Eyre, 1975), and guinea-pig (Liebig, Bernauer & Peskar, 1976). Eicosatetraynoic acid (ETA) a cyclo-oxygenase and lipoxygenase inhibitor, does not modify the immunological release of histamine or SRS-A from guinea-pig lung (Engineer, Niederhauser, Piper & Sirois, 1978).…”
Section: Introductionmentioning
confidence: 99%